Connectors (multifunctional connectors) innovation of mask connector bricks in the time of covid-19 - Mutiara T; Ratih Pratiwi; Ika Fauzia Kemalasari; Indah Purnamasari (Privietlab, 2021)
Entrepreneurship is a creative and innovative ability that is used as the basis, tips, and resources to find opportunities for success. The entrepreneurial spirit is very much needed in entrepreneurship, it can be measured through the characteristics of entrepreneurship, namely self-confidence, task and result-oriented, risk-taking, leadership, originality, and future-oriented. Such characteristics are needed to develop and maintain a business from bankruptcy. In this case the author tries to open a small business in the form of a multifunctional connector for masks and names the product Konektif (Multifunctional Connector). The product we make is made of pearls and colored beads with the aim that when used it looks very beautiful and attractive. interesting so that it can be worn as an accessory in the form of a bracelet. To market this product we also create several social media accounts such as Facebook, Instagram, Shopee, Toko Pedia and we also use a website page, there is also a website page that we create which is based on the odoo website. By using the odoo website, we hope that our newly opened venture is fluidity and its full integration will cover the needs.